Nicorandil-induced penile ulceration: a case report. (December 2016) - Yap, Darren; Aboumarzouk, Omar; Bates, Christopher
Abstract Background Penile ulceration in older patients is commonly neoplastic or infective. However, there are rarer causes of these ulcerations that we have to exclude. We present a rare complication of penile ulceration secondary to nicorandil, a nicotinamide ester. Case presentation An 86-year-old white British man was referred with a bloody discharge from under his phimotic foreskin and a lump on the shaft of his penis for the past year. He had angina which has been controlled with nicorandil for the past 5 years. A surgical biopsy of the ulcer showed inflammation with no evidence of malignancy. His penile ulceration spontaneously resolved when he stopped his nicorandil treatment. Conclusions Nicorandil-induced ulceration is a rare complication; however, it should not be missed in a clinical setting. If there is any doubt about the cause of penile ulceration, then referral to dermatology or urology for consideration of biopsy is essential.